Leakage detection in pipelines using synchrosqueeze wavelet transform - Abdul Hadi, Che Hussin (2013)
This research project is focusing on the leakage detection in the pipelines system using synchrosqueeze wavelet transform. The detection of water leakages in water distribution system has always been a challenge in the water industry as most water pipelines are laid foot underground which are normally unseen to human naked eyes until water starts to flow out from roads and creates puddles. The age in pipelines network is a major problem and the reduction of these has become a major priority for pipeline authorities around the world. Although the reasons for these leaks are well known, some of the current methods for locating and identifying them are either complicated or imprecise and most of them are time consuming. The objective in this study is to develop a test rig and conduct the experiment base on pressure transient method by identify and locate the position of the leakage occur in pipeline using signal processing synchrosqueeze wavelet transform. This project method are developed based on pressure transient by using single pressure transducer and analyses on newly method of analysing called “synchrosqueeze wavelet transform”. The first technique used the simple test rig pipeline system which in straight shape with one leakage and one outlet pipe system can identify and locate leak up to error 0.75%. The second technique used U-shape design test rig with include two leakage and one outlet pipe system and the show result error 0.3% for leak 1 and 0.25% for leak 2. The effectiveness of the proposed technique has shown great potential to locate a leak. The analysis by using synchrosqueeze wavelet transforms can be considered the first application to leak detection and location. For recommendation in this study by apply the methodology of leakage detection in pipeline at street pipeline site at real distribution network based on transient signal by using single pressure transducer at the pipe hydrant